KEMAMPUAN BERPIKIR KRITIS SISWA UNGGULAN KELAS X MAN 2 MODEL PEKANBARU PADA PEMBELAJARAN BIOLOGI TAHUN AJARAN 2015/2016 - Sri Purwanti; Evi Suryawati; Darmadi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research to give a description abaut the capacity to think criticall students class seed X MAN 2 Model Pekanbaru the academic year 2015 and 2016 .This study was conducted for the month of may-june 2016 .Samples to this research was superior a class X as many as 24 students . Instruments used to gather the data was the competence daily basis , the raport biology at first semester , the survey covered , the survey open , and the test think criticall .The survey covered consisting of 30 items wich consists of 5 indicators , the ability to analyze , synthesizing , solving the problem , concluding , evaluate and assess. After undergone a validity and reabilitas at the two all items chief closed expressed valid and reliabel .But should tests the ability of think critically consists of cognitive domain C4 C5 and C6 , the data collected analyzed a sort of descriptive set . But the ability to think critically students man 2 model pekanbaru chief obtained through closed as follows: ability to analyze 3.4 , synthesizing 3.5 , know and solve problems 3.4 , concluded 3.4 , evaluate or judging from the five 3.4 the indicators students have good showed criteria . To test the capacity to think about critical of the cognitive C4 70.8 %, C5 62.9 % and C5 53.3 % the percentage shows students have increased is think critically. While relations academic ability to the ability of think critically students received a value of rhitung > rtabel namely by rhitung 0.5456 and rtabel 0.404 showed that there is a relationship with criteria and between the ability academic students and the capacity to think critical students in learning biology.Key Words: The Capacity To Think Critically, Class Seed, Academic Performance.